Intravenous ketamine for severe alcohol use disorder at Moi Teaching & Referral Hospital, Kenya: a case report - Florence Jaguga; Philip Kirwa; Benson Gakinya; Imran Manji; Thomas Andale; Daniel Kinyanjui; Edith Kamaru Kwobah; Felicita Mwangi; Kituyi Werunga; Josephat Kerema; Charles Kwobah; Eunice Temet; et al. (BMC, 2023)
Abstract Background Alcohol use disorder is prevalent globally and in Kenya, and is associated with significant health and socio-economic consequences. Despite this, available pharmacological treatment options are limited. Recent evidence indicates that intravenous (IV) ketamine can be beneficial for the treatment of alcohol use disorder, but is yet to be approved for this indication. Further, little has been done to describe the use of IV ketamine for alcohol use disorder in Africa. The goal of this paper, is to: 1) describe the steps we took to obtain approval and prepare for off-label use of IV ketamine for patients with alcohol use disorder at the second largest hospital in Kenya, and 2) describe the presentation and outcomes of the first patient who received IV ketamine for severe alcohol use disorder at the hospital. Case presentation In preparing for the off-label use of ketamine for alcohol use disorder, we brought together a multi-disciplinary team of clinicians including psychiatrists, pharmacists, ethicists, anesthetists, and members of the drug and therapeutics committee, to spearhead the process. The team developed a protocol for administering IV ketamine for alcohol use disorder that took into account ethical and safety issues. The national drug regulatory authority, the Pharmacy and Poison's Board, reviewed and approved the protocol. Our first patient was a 39-year-old African male with severe alcohol use disorder and comorbid tobacco use disorder and bipolar disorder. The patient had attended in-patient treatment for alcohol use disorder six times and each time had relapsed between one to four months after discharge. On two occasions, the patient had relapsed while on optimal doses of oral and implant naltrexone. The patient received IV ketamine infusion at a dose of 0.71 mg/kg. The patient relapsed within one week of receiving IV ketamine while on naltrexone, mood stabilizers, and nicotine replacement therapy. Discussion & conclusions This case report describes for the first time the use of IV ketamine for alcohol use disorder in Africa. Findings will be useful in informing future research and in guiding other clinicians interested in administering IV ketamine for patients with alcohol use disorder.